Large-Scale Dryland Cropping Systems - A. Schlegel; L. Haag; D. O'Brien (Kansas Agricultural Experiment Station Research Reports, 2016)
This study was conducted from 2008 to 2015 at the Kansas State University Southwest Research-Extension Center near Tribune, Kansas. The crop rotations evaluated were continuous grain sorghum (SS), wheat-fallow (WF), wheat-corn-fallow (WCF), wheat-sorghum-fallow (WSF), wheat-corn-sorghum-fallow (WCSF), and wheat-sorghum-corn-fallow (WSCF). All rotations were grown using no-till practices except for WF, which was grown using reduced-tillage. Precipitation capture efficiency was not greater with more intensive rotations. Wheat yields were not affected by length of rotation. Corn and grain sorghum yields were about 60% greater when following wheat than when following corn or grain sorghum. Grain sorghum yields were almost twice as great as corn in similar rotations. The most profitable cropping system was wheat-sorghum-fallow.
Keywords: large-scale dryland cropping systems; conventional tillage; no-till; wheat; fallow; corn; sorghum